2022
DOI: 10.3390/su142013528
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Destination Branding in Tourism: A Systematic Review of the Literature

Abstract: Under the impact of technological innovations, particularly the Internet, ways of communication have been changing. In fact, social media has been offering virtual communities and networks that enable the creation and dissemination of information, ideas, interests, and other forms of expression. Furthermore, it clearly plays an important role in the communication strategy of the various stakeholders of the tourism industry. It is vital to create and maintain destination branding not only traditionally but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Using the approach of the International Union for Conservation of Nature [66], these 30 selected countries/destinations are defined as sustainable due to their high socioeco-nomic performance and low environmental pressure footprint, presenting an overall score of more than 65% on the sustainable development index (65-75% as strong sustainability indicator, while 75-85% as very strong sustainability level) [78]. Moreover, based on Tran and Rudolf's recent research that spotted the majority of sustainable destinations to be concentrated firstly in Europe and Asia [79], 22 of this sample's sustainable destinations are in Europe (Finland, Denmark, Sweden, Norway, Austria, Germany, France, Switzerland, Ireland, Estonia, United Kingdom, Poland, Czech Republic, Latvia, Slovenia, Spain, Netherlands, Belgium, Portugal, Hungary) while the remaining eight are located in Asia (Japan, Republic of Korea, Singapore, New Zealand, Thailand, Vietnam, China) as presented in the Sustainable Development Report Rankings 2022 [77].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the approach of the International Union for Conservation of Nature [66], these 30 selected countries/destinations are defined as sustainable due to their high socioeco-nomic performance and low environmental pressure footprint, presenting an overall score of more than 65% on the sustainable development index (65-75% as strong sustainability indicator, while 75-85% as very strong sustainability level) [78]. Moreover, based on Tran and Rudolf's recent research that spotted the majority of sustainable destinations to be concentrated firstly in Europe and Asia [79], 22 of this sample's sustainable destinations are in Europe (Finland, Denmark, Sweden, Norway, Austria, Germany, France, Switzerland, Ireland, Estonia, United Kingdom, Poland, Czech Republic, Latvia, Slovenia, Spain, Netherlands, Belgium, Portugal, Hungary) while the remaining eight are located in Asia (Japan, Republic of Korea, Singapore, New Zealand, Thailand, Vietnam, China) as presented in the Sustainable Development Report Rankings 2022 [77].…”
Section: Methodsmentioning
confidence: 99%
“…As a result, an ad hoc Instagram account was generated to follow the 200 influencers [79]. As a result, 10 popular macro-travel influencers-a new type of influencer specialized in traveling with 50,000-150,000 followers on Instagram, that present a level of engagement of more than eight and likes per post of more than 20,000-were selected to form the independent variable [79].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The various destinations and travel platforms included in the study showed a better understanding of destination branding strategies, creative content, and destination identity as driving factors in destination promotion. The choice of destination branding must be in line with its potential, representing attractions and values while showcasing the uniqueness that sets it apart from other destinations (Tran &;Rudolf, 2022;Seraphin et al, 2018).…”
Section: Brandingmentioning
confidence: 99%